ANALISIS PERHITUNGAN PENYUSUTAN ASET TETAP KOMERSIAL DAN FISKAL SERTA PENGARUHNYA DALAM LAPORAN KEUANGAN PADA PT. BANGUN KALIMANTAN SAMARINDA - nova; Agus Riyanto (OBOR: Oikonomia Borneo, 2021)
The purpose of this research is to compare the calculation of depreciation of commercial fixed assets with fiscal at PT. Build Kalimantan. The method used in this study is a comparative descriptive method, with the analytical tool used in the form of a List of Fixed Assets PT. Bangun Kalimantan (Special for Buildings and Vehicles), table of Fixed Assets Depreciation Rates According to taxation Law No.36 article 11 of 2008 concerning income tax, and Comparative Table of Depreciation of Fixed Assets. From the results of the analysis, it is known that the calculation of depreciation of fixed assets carried out by PT. Bangun Kalimantan has complied with tax laws and regulations No.36 article 11 of 2008 using the straight-line method and its useful life is in accordance with tax regulations, so there is no positive or negative correction